All types of inequality are not created equal: divergent impacts of inequality on economic growth - Stephanie Seguino (Levy Economics Institute of Bard College, 2005)
Evidence of an increase in various forms of inequality since the 1970s has motivated research on its relationship to growth and development. The findings of that research are contradictory and inconclusive. One source of these divergent results is that researchers rely on different group measures of inequality. Inequality by gender, household, class, and ethnicity may produce divergent effects on growth since they operate on macroeconomic outcomes via alternative pathways. Further, even within groups, the effect of inequality on growth depends on the measure used. For example, inequalities in capabilities (such as education and health status) may operate differently on growth than inequality in wages and income. This paper explores the different conceptual approaches to measuring between-group and within-group inequality and delineates the sometimes contradictory pathways by which these measures affect economic growth and development. The typology is applied to the cases of East Asia and Latin America. Keywords: Gender ; ethnicity ; inequality ; economic growth
Keywords: O4; E12; F16; J15; J16; 330